Human DNA ligase I (LIGI) gene and risk of cervical cancer in North Indian women - Kaur, S. (Experimental Oncology, 2013)
Aim: DNA repair genetic polymorphisms may affect cancer susceptibility as genetic variations in DNA repair genes may influence DNA repair capacity. In the present study, the association of polymorphic forms of DNA repair gene, DNA ligase I (LIGI) was examined with the risk of cervical cancer in case of North Indian women. Materials and Methods: Polymorphism was determined by polymerase chain reaction — restriction fragment length polymorphism (PCR-RFLP) method and risk of cervical cancer was evaluated by calculating odds ratios (ORs) and 95% confidence interval (CI) using a multivariate logistic regression analysis. Results: No association was found between variant forms (AC, AA) of LIGI gene and risk of cervical cancer (OR — 0.8, 95% CI 0.46–1.53 and OR — 1.0, 95% CI 0.51–2.06, respectively). However, increased but statistically non-significant risk of adenocarcinoma was observed for cervical cancer patients having AC (OR — 4.6, 95% CI 0.62–33.82) and AA (OR — 5.0, 95% CI 0.63–39.58) genotypes. Conclusion: It can thus be concluded that there is no association between LIGI polymorphisms and cervical cancer risk. However, they may be playing an important role in modulating the risk of cervical adenocarcinoma in North Indian women. Further investigations in larger studies need to be carried out for more analysis.